2017
DOI: 10.5014/ajot.2018.019919
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Processing in the General Population: Adaptability, Resiliency, and Challenging Behavior

Abstract: The results indicated that sensory avoiding predicts externalizing behaviors, depression, resiliency, and adaptability. In addition, sensory seeking is related to depression and resiliency, whereas sensory sensitivity is related to externalizing behaviors. Implications for occupational therapy research and practice are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 32 publications
3
28
0
1
Order By: Relevance
“…Behavioral self-regulation refers to how they manage sensory stimuli, ranging from passive to active behavior. These two continuums interact to create four sensory processing patterns [ 21 ]. According to the ICF-CY, DSPF focuses mainly on the interactions that are established between the person and the environment [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral self-regulation refers to how they manage sensory stimuli, ranging from passive to active behavior. These two continuums interact to create four sensory processing patterns [ 21 ]. According to the ICF-CY, DSPF focuses mainly on the interactions that are established between the person and the environment [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…San Diego: Academic Press. Dean, E. E., Little, L., Tomchek, S., & Dunn, W. (2018). Sensory processing in the general population:…”
Section: рис 7 порівняння вибірки дітей з рас та нормотипових дітейmentioning
confidence: 99%
“…Багатьох сучасних науковців цікавить питання порушень сенсорної інтеграції. Зокрема, вивчаються відносини між певними типами сенсорних моделей обробки інформації, складною поведінкою та захисними факторами (Dean, Little, Tomchek & Dunn, 2018). Описується взаємозв'язок між сенсорною обробкою та ігровою діяльністю (Roberts, Stagnitti, Brown & Bhopti, 2018); між сенсорною обробкою та порушеннями сну (К.…”
unclassified
“…This was probably due to the fact that reports had indicated that up to 95% of children with ASD showed probable or definite sensory integration difficulties [13,14]. However, it is important to remember that apart from the children with ASD, there are many with and without diagnoses who struggle in school and with everyday life due to problems in sensory integration [7,[15][16][17]. It has been estimated in the USA that 5-16% of children have difficulties processing and integrating sensations that affect their everyday life [16,17].…”
Section: Introductionmentioning
confidence: 99%